(untitled) (Sociologisk Forskning, 2019)
On academic housekeeping and its allocation Academic housekeeping denotes the type of work tasks within university departments that are low-status, time-consuming, largely invisible, and that nevertheless need to be done. This article discusses academic housekeeping in a Swedish context, and holds that this topic has been overlooked in research. The aim is therefore to specify the meaning of the concept, to describe the gendered aspects of how academic housekeeping tasks are distributed, and to discuss possible explanations for the identified pattern. Through a close reading of current scholarship, the article finds that women carry out a disproportionate share of academic housekeeping tasks. This pattern is attributable to a complex set of factors, among them ”publish or perish”-related competitive academic culture, researcher ideals, and gender norms. The main argument of the article is that unbalanced academic housekeeping allocation may partially account for women’s difficulties in advancing within academia, and therefore need to be taken seriously in research as well as in academic leadership.